Current therapy in congestive heart failure: Non-pharmacological treatment vs drug therapy - Gomes, Vitória Luciana Barbosa (2023)
The literature review proposed in this study is intended to deal with the non-pharmacological alternatives and the available drug options for the treatment of congestive heart failure (CHF). The research was, therefore, carried out in the databases of the Brasil Scientific Electronic Library (Scielo), PubMed, Latin American Literature in Health Sciences (Lilacs), Virtual Health Library (BVS), based on the following guiding question: What is the difference in prognosis of patients with congestive heart failure on drug therapy (IECA e ARA II) vs non-drug therapy? As results, it is concluded that such a prognosis depends on both therapeutic pathways, since the treatment of CHF demands treatments that seek to alleviate and control the symptoms, as well as guarantee quality of life for the patients.